The value of protocols: the experience about a facial trauma protocol applied in the emergency room in a research and teaching hospital in the north part of Italy - Clara Sina; Laura Castoldi; Ornella D'Orto; Silvana Castaldi (SAGE Publishing, 2012)
This short paper describes the introduction of a clinical pathway for cranio-facial trauma (CFT) in an emergency room of a big research and teaching hospital.